Kinetics of polymerase chain reaction positivity in patients with Clostridioides difficile infection. (October 2021) - Saha, Srishti; Yadav, Devvrat; Pardi, Ryan; Patel, Robin; Khanna, Sahil; Pardi, Darrell
Background: Polymerase chain reaction (PCR) is a sensitive test for diagnosing Clostridioides difficile infection (CDI) and could remain positive following resolution of CDI. The kinetics of PCR positivity following antibiotics for CDI is unknown. We studied this and whether it predicted CDI recurrence. Methods: Adults with CDI from October 2009 to May 2017 were included. Serial stool samples within 60 days of treatment were collected. Recurrent CDI was defined as diarrhea after interim symptom resolution with positive stool PCR within 56 or 90 days of treatment completion. Contingency table analysis was used to assess the risk of recurrence. Results: Fifty patients were included [median age: 51 (range = 20–86) years, 66% women]. Treatment given was metronidazole, 50% (25); vancomycin, 44% (22); both, 4% (2); and fidaxomicin, 2% (1). Median duration of treatment for all 50 patients was 14 (range = 8–60) days. The median duration of treatment in patients who got prolonged therapy (>14 days) ( n  = 10) was 47 (range = 18–60) days. Median time to negative PCR was 9 (95% CI, 7–14) days from treatment initiation, which did not differ by antibiotics given ( p  = 0.5). A positive PCR during or after treatment was associated with a higher risk of recurrence at 56 days ( p  = 0.02) and at 90 days ( p  = 0.009). Conclusion: The median time to negative PCR in CDI was 9 days from treatment initiation. The PCR positivity during or after treatment may be useful for recurrence prediction; larger studies are needed to validate these results.